Head Injury in Children: Has a Change in Circumstances Caused an Increase in Treatment Numbers?. (August 2015) - Pal'a, Andrej; Kapapa, Melanie; Posovszky, Carsten; Röderer, Götz; König, Ralph; Woischneck, Dieter; Wirtz, Christian Rainer; Kapapa, Thomas
The number of hospitalizations for head injuries in children is rising. The exact causes remain unclear. We analyzed data of children aged between 0 and 18 years who sustained a head injury between 2010 and 2011. The analysis focused on data related to demographics, trauma mechanism, clinical course, results of imaging scans, concomitant injuries, and outcome. A total of 794 inpatient cases of head injury were treated. The leading mechanism of injury was a fall (at home) primarily at the age of 1 to 4 years (46.5%), with the majority of the children sustaining a mild brain injury (764, 96.2%). Neurosurgery was performed in 21 (2.64%) cases; average hospital stay was 2.9 days (range: 0-68 days). This study is not able to confirm that children are increasingly being brought to the hospital by their parents because of new trauma mechanisms or parents' uncertainty, nor can we confirm that the number of nonaccidental injuries is rising.